Water Resources in the Southern Badniyah (Semi Desert) of Iraq and their Utilizations - Al-Khafaji, Sarhan Naeem (Al-Adab Journal, 2015)
Water resources play an important role in human lives as they are considered an essential source for drinking water, irrigating agricultural lands and other daily uses. Hence come this study to shed light on the major water resources in the region of southern Badiyah of Iraq which is generally distinguished by scarcity of surface water as its dominant valleys, which are considered the only source for surface water, are dry and their water flow begins when it rains heavily for a long time. In addition, the seasonal water accumulates for a short period of time in pools and depressions such as Al-Sulaibat, Al-Salman, Al-Shabjah and other depressions prevailing in most parts of the Badiyah and soon they are waterless and turn into arid lands. This has an evident effect on the region and accordingly it becomes necessary to compensate for the occurring deficiencies with the underground water especially as it has abundances in such water; therefore, there is a necessity to make policies and strategic plans to exploit water in it. This study has highlighted this region's physical elements of structure, surface, climate, soil and water & climate balance for their direct and indirect link with the lives of the people living on it and the effect they have on them